Application of the KDD process for the visualization of integrated geo-referenced textual data from the pre-processing phase - Gomez F. (2018)
The present work was achieved thanks to the joint work with my advisor, for her persistence and tenacity at the moment of sharing her teachings with me, to my distinguished teachers who have forged knowledge from the first day of classes, whom with nobility and enthusiasm influenced as an example in me and my colleagues in the master’s degree in computer science; also thanks to CONCYTEC, FONDECYT and Cienciactiva for the support and opportunities provided that made this work possible.